SYNERGY OF DIGITAL BRANDING AND INFORMATION TECHNOLOGY IN INCREASING THE COMPETITIVENESS OF ISLAMIC-BASED MSMEs - Nissa'a, Maylani Kholifatun; Mayani, Desinta Sandra Nor; Izzullana, Naqiya Nawaya; Amanda, Najwa Sabita (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
In the context of accelerating digital transformation, this article highlights the strategic potential of synergy between digital branding and information technology (IT) as a lever for the competitiveness of Islamic-based Micro, Small, and Medium Enterprises (MSMEs). Data from the Ministry of Cooperatives and SMEs (2024) reveals that only 38% of the 65 million MSMEs in Indonesia have been digitized, leaving a significant gap in exploiting digital market opportunities. Digital branding serves as a strategic tool for building a strong brand identity, while information technology provides the necessary infrastructure for efficient operations. In the context of Islamic economics, MSMEs have great potential to utilize sharia principles in their business strategies, which not only enhances competitiveness but also contributes to societal welfare. The results of this study indicate that collaboration between digital branding and information technology can strengthen brand image, improve operational efficiency, and expand market reach.